Drug fever—an immune-mediated delayed type hypersensitivity reaction to Vinca alkaloids in pediatric oncology patients, possibly mediated by cysteinyl leukotrienes - Kidon, Mona I.; Haj Yahia, Soad; Abebe-Campino, Gadi; Agmon-Levin, Nancy; Yelon, Michal (Frontiers in Allergy, 2024)
BackgroundDrug hypersensitivity reactions are common in pediatric hemato-oncology patients due to multiple factors including immune compromise and pharmacological complexities. Fever can signify severe delayed-type hypersensitivity reactions such as drug reaction with eosinophilia and systemic symptoms (DRESS) or drug-induced hypersensitivity syndrome (DIHS). The etiology of fever as an isolated hypersensitivity reaction to chemotherapeutic agents not fully understood. Here, we report three children with intracranial neoplasms experiencing recurrent febrile reactions following Vinca alkaloid-based chemotherapy, mitigated by cysteinyl leukotriene receptor antagonist therapy.MethodsWe present a series of pediatric patients with diverse intracranial neoplasms who developed recurrent fever episodes after multiple courses of Vinca alkaloid-based chemotherapy. Treatment involved prophylactic and post-chemotherapy administration of a cysteinyl leukotriene receptor antagonist to prevent fever episodes and enable completion of chemotherapy regimens without protocol modifications or desensitization.ResultsAll three patients experienced fever consistent with delayed-type hypersensitivity reactions to Vinca alkaloids. Prophylactic use of the leukotriene antagonist Montelukast successfully prevented fever recurrence, allowing uninterrupted completion of chemotherapy courses.ConclusionOur findings suggest that Montelukast, a leukotriene antagonist, may be beneficial in managing fever as a delayed-type hypersensitivity reaction to Vinca alkaloids in pediatric patients. Further research is warranted to elucidate the underlying mechanisms and leukotriene pathways involved in drug-induced fever reactions.